(untitled) (Global Business Management Review (GBMR), 2024)
The study investigated credit accessibility among small and medium sized enterprises (SMEs) in Osun state, Nigeria. Specifically, the study analyzed factors that influences SMEs’ access to credit and ascertained the extent to which government institutional funds and credit schemes have contributed to the accessibility of credit by SMEs in Osun State. Descriptive survey research design was employed for the study. A total of 238 small and medium- sized enterprises were randomly selected for the study. Data was obtained through the use of a structured questionnaire. Both descriptive statistics and logit regression model were used to analyze the data obtained. The result shows that government institutional funds have a positive significant (P < 0.05) influence on credit accessibility by small and medium- sized enterprises in the study area. The study also revealed that high bank interest rates and high level documentation have significant ((P < 0.05) negative effect on accessibility of funds by small and medium- sized enterprises. The study therefore recommends that government should put policy measures in place to regulate the interest rate charged by banks on SME loans. Secondly, government, financial institutions, and other stakeholders need to take proactive measures to facilitate credit accessibility for SMEs.